THE MATHEMATICAL MODELING FEATURES OF ELECTROMECHANICAL SYSTEMS WITH DC MOTORS - Kedria, M. M. (Science and Transport Progress, 2007)
The article examined the terms at which transients in electromechanics are examined systems with the engines of direct current most exactly reflect properties of engines from point of changes of electromagnetic and mechanical energies. Of recommendation of the use of the considered method at the construction of mathematical models is given.